Diversidade linguística em aulas de português na modalidade educação de jovens e adultos no contexto da tríplice fronteira - Pereira, Elisena Bertotti (2019)
This research studies the treatment of the diversity of languages in Portuguese classes in the modality of Education of Youths and Adults, in Foz do Iguaçu, in the context of the Triple Border. The aim of the research was to identify manners to manage multilingualism and to understand linguistic diversity critically by empirical and theoretical bias. The theoretical-methodological course was based on Linguistic Policy articulated to qualitative research, since it was intended to identify and understand the actions towards languages as a historical process. Thus, the procedures were ethnographic, in which a sociolinguistic diagnosis was carried out among students, observations in the classroom along with field diary and interviews with teachers, which are very important to problematize the school space. The theoretical basis was built from the contributions of the field of Linguistic Policy as an articulating area of other disciplines and we used the contributions of Altenhofen and Oliveira (2011); Beisiegel (1992); Bordieu (2008); Bortoni-Ricardo (2008); Calvet (2007); Di Pierro (2015); Freire (1981);Grooso (2010);Haesbaert (2007); Ludke and André (1986); Ribeiro Da Silva (2013); Sousa and Roca (2015); among others. After having performed the procedures mentioned along with the theoretical support, it was noticed that despite the lack of training to meet the needs of the border context, teachers’ value and promote the linguistic diversity present in the school environment. From the identification and understanding of the actions toward the language (s) in the Portuguese classes of the youths and adults education teaching modality, it is suggested possible propositions and referrals for the valorisation and promotion of linguistic diversity in the field of the classroom, of education, and of public policy.